AAGBS Annual Report 2021: AAGBS KPI & PI achievements - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
AAGBS have 8 key performance indicators (KPI) and 38 performance indicators (PI).